Influence of Living Sunnah on Customers Satisfaction Basmalah Store Malang with Service Quality as Moderating Variables - Safitri, Wulan Nur; Aliyah, Faizatul; Rofiq, Aunur (Social Sciences Journal, 2023)
One way to increase Customers Satisfaction is by applying the "Living Sunnah Dagang" concept, which prioritizes sunnah practices in every aspect of business, including retail businesses. Basmalah Malang Store prioritizes Customers Satisfaction by providing friendly, responsive, and professional service. Every sales team member in this store is trained to understand customer needs and preferences and provide appropriate and satisfactory solutions. They are also encouraged always to respect customers and communicate politely and honestly. So this study will examine the direct influence of Living Sunnah Dagang on Service Quality and Customers Satisfaction and the influence of Living Sunnah Dagang on Customers Satisfaction through Service Quality. This study uses the descriptive, explanatory method using path analysis in its testing and SPSS 22 calculations. The results of this study show that there is a positive and significant direct influence of Living Sunnah Dagang variables on Service Quality of 0.304 or 30.4% and a positive and significant indirect influence of Living Sunnah Dagang on Customers Satisfaction through Service Quality of 0.101 or 10.1%. So this study will examine the direct influence of Living Sunnah Dagang on Service Quality and Customers Satisfaction and the influence of Living Sunnah Dagang on Customers Satisfaction through Service Quality. This study uses the descriptive, explanatory method using path analysis in its testing and SPSS 22 calculations. The results of this study show that there is a positive and significant direct influence of Living Sunnah Dagang variables on Service Quality of 0.304 or 30.4% and a positive and significant indirect influence of Living Sunnah Dagang on Customers Satisfaction through Service Quality of 0.101 or 10.1%. So this study will examine the direct influence of Living Sunnah Dagang on Service Quality and Customers Satisfaction and the influence of Living Sunnah Dagang on Customers Satisfaction through Service Quality. This study uses the descriptive, explanatory method using path analysis in its testing and SPSS 22 calculations. The results of this study show that there is a positive and significant direct influence of Living Sunnah Dagang variables on Service Quality of 0.304 or 30.4% and a positive and significant indirect influence of Living Sunnah Dagang on Customers Satisfaction through Service Quality of 0.101 or 10.1%.